Characteristics and Influencing Factors of Soil CH4 and N2O Fluxes in Typical Broad-leaved Forests in the Yangtze River Delta Region, China - JIA Qinqi; XU Fei; CHEN Bingjiang; LU Yanran; CHEN Lihan; HU Jiahao; GUO Na; FANG Shuangxi (Shuitu Baochi Xuebao)
[Objective] The forest coverage rate in the Yangtze River Delta region reaches 33.4%, and the underlying surface soil may have an important impact on the regional greenhouse gas budget. To explore the characteristics of changes in CH4 and N2O fluxes in the forest ecosystem soil in this region, as well as the effects of soil physicochemical properties and litter on these two greenhouse gas fluxes. [Methods] Taking the typical broad-leaved forest soil in Hangzhou, Zhejiang Province as the research object, soil-air interface CH4 and N2O fluxes were continuously measured from November 2022 to November 2023 by the static chamber-gas chromatography method. [Results] The average annual absorption fluxes of CH4 in the soil without litter (S) and soil with litter (SL) treatments were (47.82±18.54), (36.80±13.55) μg/(m2·h), as well as the average emission fluxes of N2O were (80.74±45.24), (52.70±25.98) μg/(m2·h), respectively. The seasonal variations of CH4 absorption fluxes were similar under the two treatments of S and SL, with the absorption flux in spring and summer being higher than that in autumn and winter. The N2O emission fluxes of the two treatments also showed similar seasonal variations, with the highest in summer, followed by spring, and lower in autumn and winter. Litter had a significant impact on CH4 absorption and N2O emissions, with litter remove leading to a 29.9% increase in CH4 influx and a 53.2% increase in N2O efflux. Correlation analysis revealed that the CH4 absorption flux and N2O emission flux under the two treatments were significantly positively correlated with soil organic carbon content and soil temperature, respectively (p<0.05). The CH4 absorption flux had a significant negative correlation with soil bulk density under SL treatment (p<0.05). [Conclusion] The research results indicate that broad-leaved forests have an important role in forest carbon sinks, and the management of soil litter in broad-leaved forest is crucial for balancing CH4 absorption and N2O emissions, as well as mitigating climate warming.